GENETIC VARIABILITY , EXPECTANT GENETIC ADVANCE AND PHENOTYPIC CORRELATION FOR YIELD AND ITS COMPONENTS IN SUMMER SQUASH (Cucurbita pepo L.) - Majid K. Al-Kummer (Mesopotamia Journal of Agriculture)
An experiment was conducted in the Field of Horticulture and landscape design department , College of Agriculture and Forestry Mosul University during spring and autumn seasons of 2006 to estimate the genetic and aspectual variability to the yield and its components by using six summer squash varieties viz., (Local , Middle East, Syrian , Zucchini , Tala and Bather Elbethor).The investigation revealed high variability between varieties for all studied characters , and variety Tala was highly superior for yield , fruit number / plant , fruit length and weight. There was a high genetic variation for fruit weight and plant length. High heritability for plant length, number of days for staminate and pistil late flower production , fruit length and weight which is due to the high variability among these characters. There was a high positive and significant correlation coefficient between yield and fruit weight , fruit diameter , number of fruits / plant and sex expression ratio.